Inflated how money and debt built the American dream - Whalen, R. Christopher, 1959- (Hoboken, N.J. : Wiley, 2011)
"Americans as a whole view themselves as reasonably prudent and sober people when it comes to matters of money, reflecting the puritan roots of the earliest European settlers. Yet as a community, we also seem to believe that we are entitled to a lifestyle that is well-beyond our current income, a tendency that goes back to the earliest days of the United States and particularly to get rich quick experiences ranging from the Gold Rush of the 1840s to the real estate bubble of the early 21st Century. Inflated examines this apparent conflict and makes the argument that such a world view is so ingrained in us that to expect the United States to live in a "deflated" world is simply unrealistic. It skillfully seeks to tell the story of, money inflation and public debt as enduring (and perhaps endearing) features of American life, rather than something we can one day overcome as our policy makers constantly promise. Features interviews with today's top financial industry leaders and insiders. Offer a glimpse into the future of the Federal Reserve and the role it will play in the coming years. Examines what the future may hold for the value of the U.S. dollar and the real incomes of future generations of Americans. The gradual result of the situation we find ourselves in will inevitably lead to inflation, loss of economic opportunity, and a decline in the value of the dollar. This book will show you why, and reveal how we might be able to deal with it."--
Machine generated contents note: Preface. -- Acknowledgments. -- Chapter One Free Banking and Private Money. -- The Bank of the United States. -- State Debt Defaults. -- The Age of Andrew Jackson. -- The Panic of 1837. -- The Gold Rush. -- The Rise of Bank Clearinghouses. -- Chapter Two Lincoln Saves a Nation by Printing Money. -- The Lincoln Legacy. -- Financing the War. -- Salmon Chase and Jay Cooke. -- Fisk & Gould Profit by Inflation. -- The Panic of 1873. -- Gold Convertibility Restored. -- The Battle Over Silver Money. -- A Changing American Dream. -- The Silver Compromise. -- Chapter Three Robber Barons and the Gilded Age. -- The Age of Speculation. -- Republicans Embrace Inflation. -- The Panic of 1893. -- The Cross of Silver. -- The Evangelical Silverites. -- The Turning Point: 1896. -- Chapter Four The Rise of the Central Bank. -- The Trust Buster: Theodore Roosevelt. -- The Need for a Flexible Currency. -- The Crisis of 1907. -- The National Monetary Commission. -- The Passage of the Federal Reserve Act. -- Roosevelt, Wilson and the Politics of Reform. -- Chapter Five War, Boom & Bust. -- The Fed During WW I. -- A Return to Republican Normalcy. -- The Roaring Twenties. -- The New Era of Debt and Investing. -- The Bust: Stocks Fall and Tariffs Rise. -- Chapter Six New Deal to Cold War. -- FDR and the Era of Broken Precedent. -- The Seizure of Gold and Dollar Devaluation. -- Dollar Devaluation Hurt World Trade. -- The Rise of the Corporate State. -- Central Planning Arrives in Washington. -- FDR Embraces Federal Deposit Insurance. -- The Legacy of FDR. -- The Fed and The RFC. -- Corportivist Reform at the Fed. -- The New Deal Fails, So America Goes to War. -- Wartime Inflation and Debt Finance. -- Bretton Woods and Global Inflation. -- Chapter Seven Debt and Inflation A Rising Tide Lifts All Boats. -- Federal Revenues Grow. -- The Fed Regains Independence. -- The Post-War Economy Soars. -- The Legacy of War. -- Cold War, Free Trade. -- The Dollar's Golden Age. -- Global Imbalances Return. -- Richard Nixon's Betrayal. -- The End of the Dollar Peg. -- The Return of Sovereign Borrowing. -- Chapter Eight Leveraging the American Dream. -- The New Uncertainty. -- Humphrey Hawkins and Full Employment. -- Balanced Budgets and Inflation. -- Volcker's Shock Treatment. -- The Crisis Managers. -- The Latin Debt Crisis. -- Volcker's Apprentice: Gerald Corrigan. -- Reagan Reappoints Volcker. -- The Never-ending Crisis. -- Volcker Exits and Crisis Returns. -- From Excess to Delusion. -- The Greenspan Legacy. -- Chapter Nine Prospects. -- The Growth Challenge. -- Growth versus Inflation. -- Changing Places. -- Triffin's Dilemma and the Dollar. -- Notes. -- About the Author. -- Index.
Includes bibliographical references (p. 365-368) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Debts, Public -- United States; Inflation (Finance) -- United States; Money -- United States -- History; Monetary policy -- United States -- History; Electronic books